There goes our family friendly neighborhood: Residents' perceptions of institutionally driven inner-city revitalization in Buffalo, NY. Issue 2 (3rd April 2019) - Silverman, Robert Mark; Taylor, Henry Louis; Yin, Li; Miller, Camden; Buggs, Pascal
ABSTRACT: This article examines residents' perceptions of inner-city revitalization in legacy cities. The analysis focuses on neighborhoods undergoing revitalization in a legacy city, Buffalo, NY. The article draws from data for a larger research project called Turning the Corner which was sponsored by the Urban Institute. The focus of that project was to identify planning strategies to address negative externalities caused by neighborhood change and heightened risks of displacement due to revitalization. Data were collected through a series of focus groups with residents and stakeholders in working-class, minority neighborhoods which were identified as being in the early stages of revitalization. Two findings emerged from the analysis. First, residents perceived urban revitalization to have a destabilizing effect on traditional neighborhoods. Second, residents perceived revitalization as detrimental to the sustainability of family-friendly neighborhoods. Insights from the analysis are used to prompt planners' advocacy for revitalization strategies aimed at protecting minority, working-class neighborhoods when institutionally driven revitalization occurs.